1965
DOI: 10.1139/v65-241
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Biochemistry of Microorganisms: Part 117. Sepedonin, a Tropolone Metabolite of Sepedonium Chrysospermum Fries

Abstract: Two yellow substances were isolated from culture filtrates of the fungus Sepedoniuna chrysospermunz Fries. One of these, named sepedonin, predominates in growing cultures and is believed t o be the direct product of metabolism. The second, an anhydro derivative of sepedonin, was probably formed spontaneously in the culture filtrate, and during the isolation process, by chemical dehydration. Sepedonin, C1lH1205 with one C-methyl group, gave two dimethyl ethers with diazomethane and has the spectral characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Chemical non-equivalence of the hydrogens in each methylene group (both gave characteristic broadened AB quartets, JAB -17 Hz) also indicated that they were either part of a ring system, in which no averaging of the environment occurred due to conformer interconversion, or in an otherwise asymmetric environment. Previous work (1) had also shown that anhydrosepedonin contained two phenolic-type hydroxyl groups (pK --6 and 9) and a masked carbonyl group. These functional groups are also present in sepedonin since they were not involved in its dehydration.…”
Section: Structurementioning
confidence: 87%
See 3 more Smart Citations
“…Chemical non-equivalence of the hydrogens in each methylene group (both gave characteristic broadened AB quartets, JAB -17 Hz) also indicated that they were either part of a ring system, in which no averaging of the environment occurred due to conformer interconversion, or in an otherwise asymmetric environment. Previous work (1) had also shown that anhydrosepedonin contained two phenolic-type hydroxyl groups (pK --6 and 9) and a masked carbonyl group. These functional groups are also present in sepedonin since they were not involved in its dehydration.…”
Section: Structurementioning
confidence: 87%
“…We have checked and found that the latter belief was unfounded; all three dimethyl ethers are stable and are not interconvertible. The only dimethyl ethers obtained when anhydrosepedonin was treated with base and dimethyl sulfate in acetone, or alternatively with silver oxide and methyl iodide in benzene, were A and B. Sepedonin gave dimethyl ethers A and B when reacted with diazomethane, and these were dehydrated to anhydrosepedonin dimethyl ethers A and B, respectively (1). The structures of all of these derivatives were not determined.…”
Section: Methyl Ethersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of citrinin 2 the more reduced aromatic nucleus is stable and does not rearrange. Compounds such as sepedonin 5, 84 another of the Raistraick compounds, feature structural motifs common to both the tropolones and citrinin and it seems likely that the sepedonin BGC will feature both a citB-type and a TropC-type oxidase.…”
mentioning
confidence: 99%